Pathogenic fungi-induced susceptibility is mitigated by mutual Lactobacillus plantarum in the Drosophila melanogaster model - Su, Wanzhen (BMC Microbiol, 2019)
BACKGROUND: Since animals frequently encounter a variety of harmful fungi in nature, their ability to develop sophisticated anti-fungal strategies allows them to flourish across the globe. Extensive studies have highlighted the significant involvement of indigenous microbial communities in human health. However, the daunting diversity of mammalian microbiota and host genetic complexity are major obstacles to our understanding of these intricate links between microbiota components, host immune genotype, and disease phenotype. In this study, we sought to develop a bacterium-fungus-Drosophila model to systematically evaluate the anti-fungal effects of commensal bacteria. RESULTS: We isolated the pathogenic fungal strain, Diaporthe FY, which was detrimental to the survival and development of Drosophila upon infection. Using Drosophila as a model system, Drosophila-associated Lactobacillus plantarum functioned as a probiotic, and protected the flies from mortality induced by Diaporthe FY. Our results show that L. plantarum hindered the growth of Diaporthe FY in vitro, and decreased the mortality rate of Diaporthe FY-infected flies in vivo, consequently mitigating the toxicity of Diaporthe FY to the hosts. Additionally, the presence of L. plantarum overrode the avoidance of oviposition on Diaporthe FY-associated substrates. CONCLUSIONS: Diaporthe FY was identified as a potential Drosophila pathogen. Commensal L. plantarum mitigated the susceptibility of Drosophila to pathogenic fungi, providing insight into the natural interplay between commensal and pathogenic microbial communities that contribute to animal health and pathogenesis.